(untitled) (Research, Society and Development, 2020)
This study aimed to describe recommendations for control and prevention strategies for coping with the COVID-19 pandemic, and to understand the impact of social isolation on the population. This is a descriptive study based on a literature review, with a qualitative approach, carried out by searching for articles indexed in the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Literature Latin American and Caribbean Health Sciences (LILACS). The inclusion criteria include literature review surveys covering the year 2020. The exclusion criteria were duplicate, incomplete articles, abstracts, reviews, debates, experience reports and unavailable in full. 05 articles and 04 studies referring to health entities were analyzed. The results of the study show that, the main recommendations are to wash your hands to the level of the wrists with soap and water, or to clean them with alcohol gel, when coughing or sneezing, cover your nose and mouth with a handkerchief. or with the arms. Avoid touching your eyes, nose and mouth with your hands when not cleaned; keep a minimum distance of 2 meters from people, avoid physical contact, and do not share personal objects. We conclude that the lack of information regarding the recommendations for COVID - 19 times is still insufficient, thus, social isolation comprises one of the main measures to minimize the number of cases of the disease, due to the reduced contact with society, resulting in low virus transmission capacity.